Pregnancy outcome following maternal use of zanamivir or oseltamivir during the 2009 influenza A/H1N1 pandemic: a national prospective surveillance study. (7th March 2014) - Dunstan, HJ; Mill, AC; Stephens, S; Yates, LM; Thomas, SHL
<x xml:space="preserve">Abstract</x> Objective To conduct enhanced surveillance for signals of teratogenesis following use of the neuraminidase inhibitors zanamivir and oseltamivir in the treatment or post‐exposure prophylaxis of 2009 A/H1N1 influenza during pregnancy. Design Prospective cohort study, using national surveillance data collected by the UK Teratology Information Service (UKTIS) during the 2009 A/H1N1 pandemic. Setting United Kingdom. Population Pregnant women who were reported to UKTIS by healthcare professionals seeking advice about exposure to zanamivir and oseltamivir or to other non‐teratogenic drugs. Methods Pregnancy outcomes were collected for prospectively reported pregnancies exposed to zanamivir (n = 180) or oseltamivir (n = 27), and compared with a reference group of 575 prospectively reported pregnancies exposed to non‐teratogenic drugs over the same period. Main outcome measures Rates of major congenital malformation, preterm delivery and low birth weight. Results No significant differences in overall rates of major malformation in live‐born infants [adjusted odds ratios (aOR): zanamivir 0.37 (95% confidence interval 0.02–2.70); oseltamivir aOR 0.81 (0.05, 14.15)], preterm delivery [aOR: zanamivir 0.95 (0.45, 1.89); oseltamivir aOR 1.68 (0.38, 5.38)] or low birth weight [aOR: zanamivir 0.94 (0.25, 2.90); oseltamivir aOR 4.12 (0.59, 17.99)] were observed following exposure at any gestation. No major malformations were reported in 37 zanamivir or eight oseltamivir first trimester exposures. Conclusion These surveillance data do not provide a signal that use of zanamivir or oseltamivir in pregnancy is associated with an increased risk of the adverse pregnancy outcomes studied but the data are too limited to state conclusively that there is no increase in risk.